2015
DOI: 10.18632/oncotarget.3872
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPM7 by carvacrol suppresses glioblastoma cell proliferation, migration and invasion

Abstract: Glioblastomas are progressive brain tumors with devastating proliferative and invasive characteristics. Ion channels are the second largest target class for drug development. In this study, we investigated the effects of the TRPM7 inhibitor carvacrol on the viability, resistance to apoptosis, migration, and invasiveness of the human U87 glioblastoma cell line.The expression levels of TRPM7 mRNA and protein in U87 cells were detected by RT-PCR, western blotting and immunofluorescence. TRPM7 currents were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 73 publications
12
113
1
Order By: Relevance
“…Previously, we reported that the TRPM7 mRNA and protein, as well as channel activity are upregulated in the U87 cells compared to normal human astrocytes [4]. In the current study, we found that naltriben further augmented the TRPM7-like currents in U87 cells.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previously, we reported that the TRPM7 mRNA and protein, as well as channel activity are upregulated in the U87 cells compared to normal human astrocytes [4]. In the current study, we found that naltriben further augmented the TRPM7-like currents in U87 cells.…”
Section: Discussionsupporting
confidence: 66%
“…Previously, we have shown that pharmacological block or knock-down of TRPM7 inhibited both pathways [4, 5]. In the current study, potentiation of TRPM7 by naltriben upregulated p-ERK1/2 protein levels (Figure 4A, 4C), but not p-Akt levels (Figure 4A, 4F).…”
Section: Resultssupporting
confidence: 61%
“…Among TRP channels, the transient receptor potential melastatin related 7 (TRPM7) channel is a Ca 2+ /Mg 2+ channel fused with a functional kinase domain that belongs to the α-kinase family [13], [14]. We and others showed that TRPM7 is involved in migration and/or invasion of epidermal cancer cells including neuroblastoma [15], [16], glioblastoma [17], breast cancer [18], [19], nasopharynx cancer [20], [21], lung cancer [22], prostate cancer [23], and PDAC [24], [25]. Importantly, TRPM7 is required for breast cancer metastasis formation in mouse xenograft, and high channel expression is an independent marker of poor outcome in breast cancer patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most common malignant primary brain tumor with devastating proliferative and invasive characteristics; its aggressive growth pattern led GBM patients face a poor prognosis even after having received the best available treatment modalities12342829. However, the distinct biological behavior of aggressive proliferation and invasive growth of GBM might be the unexplored therapeutic targets for treatment of this fatal tumor5.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distinct biological behavior of aggressive proliferation and invasive growth of GBM might be the unexplored therapeutic targets for treatment of this fatal tumor5. Thus, the discovery of new and specific chemotherapeutic agents inhibiting proliferation, migration and invasion of GBM cells are regarded as effective strategies to research and develop new drugs for GBM therapeutics101112131428.…”
Section: Discussionmentioning
confidence: 99%